WOMEN’S WORDS AND IMAGES IN THE SOCIALIST PARTY: THE PRESIDENTIAL CAMPAIGNS OF 1916 IN ARGENTINA - Palermo, Silvana Alejandra (Universidad Nacional del Litoral, 2018)
This study examines women’s participation in the electoral campaigns of the Socialist Party, in particular the presidential campaign of 1916. This analysis is based on a variety of sources: official documents from the Socialist Party, the Socialist press and two popular magazines, Caras y Caretas and Fray Mocho. This article argues that the notorious strength demonstrated by the Socialists to mobilize owes to their previous experience in electoral and public participation, in which women played a vital role, and also due to the fact that the commercial press became a prominent mean of communication of the Socialist creed, an appropriate instrument to make socialist women’s words and faces know to a larger public.